THE SELF-REPORTED INFLUENCE OF USING SMS LANGUAGE IN TEXTING AND SOCIAL MEDIA ON SAUDI STUDENTS’ ACADEMIC WRITING - Alharbi, Bader (PEOPLE: International Journal of Social Sciences, 2017)
SMS language is a form of written English that is often used in informal, computer-mediated communications like texting, online chat, and social media. It is known for shortening many words using acronyms and other forms of abbreviation. SMS language is increasingly well documented in the scholarly literature and its impact on students’ formal academic writing is a topic of debate. This study uses a mixed-methods approach to investigate students’ perspectives on their own use of SMS language and how it might affect their formal academic writing. The sample was composed of final-year university students who are native Arabic speakers and acquired English as a second language. The data was collected through the use of quantitative questionnaires and supplemented with semi-structured quantitative interviews. The findings revealed that virtually all participants used features of SMS language in their online communications. Still, they struggled to recognize some of the most well-documented, commonly used abbreviations. The interviews showed that time, convenience, and character limits were the primary motivators for students to use SMS language. The findings also indicated that at least some students can recall having made spelling or sentence construction errors in formal academic writing that they attribute to their reliance on SMS language in their digital communications. Further scholarly attention is strongly indicated, and possible directions for future research are described.